The Influence Of Problem-Based Learning On The Ability to Work Together And Solve Problems Of Students in Class XII Ma Al Hidayah Bangkalan PPKN Subjects - Fitriyah Fitriyah; Mustaji Mustaji; Bachtiar S. Bachri (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to 1) describe the effect of problem-based learning collaboration skills students in PPKn Class XII MA Al Hidayah Bangkalan, 2) describe the effect of Problem Based Learning on students' problem-solving skills in PPKn Class XII MA Al Hidayah Bangkalan. The method used is an experiment by comparing the results of the pre-test and post-test using two groups selected, namely the experimental group and the control group. In line with objectives 1) the results show that the problem-based learning model has an influence on students' cooperative skills in civics subject. Based on the results of data analysis which stated that there were significant differences in the cooperative skills of the two groups, it can be proven that the learning model has an influence on students' collaboration skills. In accordance with objective 2), it was found that the problem-based learning model had an influence on the problem-solving abilities of students in Civics subjects. Based on the results of data analysis which stated that there were significant differences in the problem-solving skills of the two groups, it can be proven that the learning model has an influence on students' problem-solving abilities. So it can be concluded that the Problem Based Learning learning model has the effect of increasing collaboration skills and students' problem solving skills in PPKn Class XII subjects MA Al Hidayah Bangkalan